A Brief review of the risks and the stratification of sudden death in the ventricular Pre-excitation syndrome. - Fröemming Junior, Clovis; Leiria, Tiago Luiz Luz; Lima, Gustavo Glotz de; Pires, Leonardo Martins; Kruse, Marcelo Lapa; Moreira, Thiago Camargo; Pinos, Javier Fernando Vasquez; Finkler, Bruno Schaaf; Zanotta, Danilo Barros (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Objective: The diagnosis of ventricular preexcitation syndromes is often occasional and with underestimated risk, showing controversies in its stratification and indication of prophylactic ablation. This work aims to explore and summarize the data in the literature, exposing the authors’ conclusions regarding this review. Methods: The authors prepared this work based on the latest guideline of the European Society of Cardiology plus a search for articles published in MEDLINE whose titles related to sudden death from ventricular fibrillation in patients with ventricular preexcitation. Discussion: Sudden death secondary to preexcited atrial fibrillation with degeneration to ventricular fibrillation is the most feared event in Wolff-Parkinson-White syndrome, has an average annual incidence of 0.15 to 0.39%, affecting individuals with structurally normal heart. The noninvasive stratification methods do not demonstrate adequate efficacy, and an electrophysiological study is recommended for all cases at the time of diagnosis. The most severe criteria for sudden death are shortest preexcited RR interval ≤ 250 ms (SPERRI or SPRRI); accessory pathway effective refractory period (APERP) ≤ 250 ms; presence of multiple accessory bundles; shortest paced cycle length with preexcitation during atrial pacing ≤ 250ms (SPPCL); Ebstein anomaly; induction of sustained supraventricular tachycardia. Conclusion: The low rate of complications during the diagnostic exam as well as in the therapeutic procedure, added to the high percentage of success of radiofrequency ablation, leads to indicate early the execution of electrophysiological study as a more diligent and accurate measure in the reduction of sudden death events in patients with ventricular preexcitation syndromes.